Detection and Identification of Polymorphism in Mutant Strawberry (Fragaria spp.) Plants Based on Cleaved Amplified Polymorphic Sequences Molecular Markers - Aristya, Ganies Riza; Ayundai, Melin; Putri, Fauzana; Widiastuti, Ani; Kasiamdari, Rina Sri (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
Strawberry (Fragaria spp.) has a high economic value and various benefits, but the production of strawberry plants in Indonesia is still low in terms of both quantity and quality. Strawberry plant breeding can be done in various techniques, one of which is polyploidization. Polyploidization by an induction of colchicine at various concentrations in strawberry crops cv. California and Festival resulted in superior phenotype characteristics. To prove the existence of a change in ploidy in strawberry, then research at the molecular level needs to be done. The purposes of this study were to find out changes in ploidy of strawberry plants using CAPS molecular markers and to detect the polymorphism in strawberry plants quickly. The samples used were young leaves. Main procedure was the cutting of the amplified DNA using restriction enzymes of TaqI and HaeIII. The results showed that CAPS molecular markers were capable of detecting polymorphism quickly and efficiently in strawberry plants. Specific bands among strawberry plants having undergone polyploidization and those not having undergone polyploidization can be seen on the differences in monomorphic or polymorphic bands between the control plants and treated plants.Â